Hemodynamic forces in olympic athletes assessed by cardiac magnetic resonance: a new non-invasive screening tool?. (11th May 2022) - Filomena, D; Monosilio, S; Birtolo, L I; Penza, M; Lemme, E; Squeo, M R; Di Gioia, G; Tonti, G; Pedrizzetti, G; Fedele, F; Gualdi, G; Spataro, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Non-invasive evaluation of left ventricular hemodynamic forces (HDFs) by Cardiac Magnetic Resonance (CMR) is a promising tool to improve systolic and diastolic evaluation. No data are available on athletic population. Purpose: To provide the range of normal values of HDFs in Olympic athletes and to evaluate the possible influence of different sport categories. Methods: A group of Olympic athletes evaluated prior the Olympic games with unremarkable cardiovascular pre-participation screening tests underwent CMR without contrast administration. A group of sedentary subjects was enrolled as a control group. Cine-images were post-processed by a feature-tracking based software to estimate HDFs. HDFs were measured in apex-base (AB) and latero-septal (LS) directions, over the entire heartbeat, in systole and diastole. Athletes were divided in subgroups according to ESC sport classification for comparison. They were also divided according to the ejection fraction (EF ≤ or >53%). Results: 93 elite athletes (33% power, 33% mixed, 33% endurance) were enrolled. HDFs in AB and LS direction were 20.5%± 4.3 and 2.9%± 0.7 in the entire heartbeat, 32.6% ± 7 and 3.6%± 1 in systole, 11%± 4.1 and 2.3%± 0.8 in diastole. Comparing athletes of different sport category and sedentary controls no significant differences were found between groups (Table). Comparing athletes with ejection fraction (EF) £ 53% and > 53%, the former showed lower values of AB-HDFs assessed in the entire heartbeat and in systole (18.9 ± 4.6 % vs 20.9 ± 4.1; p= 0.024 and 29.6 ± 6.3 vs 33.3 ± 7; p= 0.024, respectively), but within the normal range. Conclusion: We provide normal range for HDFs assessed by CMR in elite athletes and no differences were observed between sedentary controls and athletes involved in different sport categories. Comparing athletes with low-normal and normal ejection fraction, the former showed lower values of AB-HDFs but within the normal range.